Diagnosis of Proteus mirabilis using PCR technique and determining their sensitivity to some antibiotics. - Nuha Jawad; Syoof Khowman. Alramahy (Al-Qadisiyah Journal of Pure Science, 2018)
Proteus mirabilis The samples of the study were collected from different clinical sources 185 isolates of hospitals, the Diwaniyah city during the period from October 2015 to April and divided the samples, according to sources collected into five groups (46 swab ear, 42 swab burns, 37 a stool sample, 59  urine sample and 1 blood sample), as results showed that cultural and biochemical tests 69 isolated belong to P.mirabilis, diagnosis was confirmed by api 20E and the use of polymerase chain reaction.         Tested the sensitivity of isolates P.mirabilis about 15 types of antibiotics by disk diffusion method, and belonging to ten classes of antibiotics,That shown sensitivity first to isolates of P.mirabilis results, the proportion of resistant P.mirabils antimicrobial Î²- lactam antibiotic represented in Amoxicillin resistance and Ampicillin 84.05%, Amoxicillin/cluvanic acid 47.82%, Ticarcillin and , Cefatozidime 66.66%, Cefotaxim 53.62%, Meropenem 5.6%. The rate of resistance to antibiotics aminoglycosides represented in Amikacin resistance 17.36 %, Gentamicin percentage resistance 33.33%, Quinolones represented in Nalidic acid resistance 75.36%, while the Ciprofloxacin counted lower proportion of resistance 4.34 %, Trimethoprim resistance75.36 %.Chloramphenicol  have high     resistance rate of 82.60 %, as well as all of the Tetracycline 82.60%, and Rifampin  91.30% .